Real-world study of antiresorptive-related osteonecrosis of jaw based on the US food and drug administration adverse event reporting system database - Peng, Jing; Wang, Hui; Liu, Zhen; Xu, Zhen-Liang; Wang, Mei-Xia; Chen, Qi-Miao; Wu, Ming-Li; Ren, Xiao-Lei; Liang, Qiu-Hua; Liu, Fu-Peng; Ban, Bo (Frontiers in Pharmacology, 2022)
Objective: This study aims to explore the risk signals of osteonecrosis of jaw induced by antiresorptive drugs and provide references for the clinical safety application. Method: Based on the Food and Drug Administration Adverse Event Reporting System (FAERS) from January 2004 to September 2021, we chose "Osteonecrosis of jaw (10064658)" and "Exposed bone in jaw (10071014)" as peferred terms, " antiresorptive drugs" as the target drugs, and primary suspect drug as the drug role code in the dataset. Based on disproportionality analysis, we used reporting odds ratio (ROR) to evaluate the association between drugs and adverse events. We took the High-Level Terms (HLT) of MedDRA as the classification level of indications to calculate ROR to compare the signal difference of ONJ in different indications. In addition, clinical characteristics of patients with antiresorptive-related osteonecrosis of the jaw and the time of onset of ONJ following different antiresorptive drugs were collected. Results: The FAERS contained 18,421 reports relating to osteonecrosis of jaw from January 2004 to September 2021. A total of 8 antiresorptive agents were included in the analysis. From high to low, the ROR of ONJ induced by antiresorptive agents (regardless of indication) is pamidronate (ROR=494.8), zoledronic acid (ROR=431.9), denosumab (ROR=194.8), alendronate (ROR=151.2), risedronate (ROR=140.2), etidronic acid (ROR=64.5), ibandronate (ROR=40.8), and romosozumab (ROR=6.4). HLT ROR values for "metabolic bone disorders" were the lowest for each drug, while HLT ROR values were high for tumor-related indications " include breast and nipple neoplasms malignant, plasma cell myelomas, and prostatic neoplasms malignant. The onset time for osteonecrosis of the jaw as median (Q1, Q3) are 504.0 (238.5, 853.0), 1187.0 (511.0, 2039), 632.0 (231.5, 1108), 487.5 (150.0, 1134), 852.0 (409.5, 1594), 365.0 (181.0, 623.0), 169.5 (33.0, 335.0), and 850.0 days (850.0, 974.0) for zoledronic acid, alendronate, ibandronate, pamidronate, risedronate, denosumab, romosozumab and etidronate, respectively. Conclusion: All antiresorptive drugs may have ONJ risk. The risk of ONJ induced by the antiresorptive drugs was different for the different indications. Romosozumab may be the least risky drug. Practitioners should consider the factors that may increase the risk of ONJ.